2016
DOI: 10.1177/1043454215628002
|View full text |Cite
|
Sign up to set email alerts
|

Parent Attributions About Child Symptoms Related to Cancer Therapy

Abstract: These exploratory findings provide context to parental perception of their child's treatment-related symptoms and may contribute to a better understanding of parental perception of child and the family coping and communicating style. These findings may assist in the development of psychoeducational interventions aimed at promoting open communication styles within the family and reducing child and parent burden during treatment procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
1
12
0
12
Order By: Relevance
“…In this study, the mothers reported that their family routines were greatly affected by their child's condition. This study supports the results of other similar studies (32).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, the mothers reported that their family routines were greatly affected by their child's condition. This study supports the results of other similar studies (32).…”
Section: Discussionsupporting
confidence: 83%
“…One study found an association between more than 10 hospital days during the last month of life and lower quality of care ratings by physician (Mack et al., ). Against the background of relationship between longer hospitalisations and quality of care, the highly interrupted daily life (Bjork et al., ; Di Battista et al., ), difficulties to maintain social relationships and accompanying isolation (Enskar et al., ; Gibson et al., ; Hokkanen et al., ), and affected familial relations (Hokkanen et al., ; Patterson et al., ) especially apply to leukaemia patients. Spending more time in the hospital not only decreases the odds of benefitting from protective factors, it also magnifies children's major stressors, for example, those associated with treatment procedures, loss of control and the hospital environment (McCaffrey, ).…”
Section: Discussionmentioning
confidence: 99%
“…A cancer diagnosis marks an abrupt break in life. Lived experiences of children with cancer and their families have been described as an interrupted one with limited opportunities to engage in leisure activities and difficulties in sustaining existing friendships (Bjork, Wiebe, & Hallstrom, ; Di Battista et al., ; Griffiths, Schweitzer, & Yates, ). Cancer diagnosis of a child is often described as a loss of normal family life (Badarau et al., ; De Clercq et al., ; Patterson, Holm, & Gurney, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex, painful experience, marked by frequent medical consultations, chemotherapy, radiation, surgeries, routine exams, withdrawal from school, limitations in performing some activities, loss of opportunities, and changes in appearance and lifestyle. [18][19][20] In this case, it is necessary to provide support and comfort, especially when the child complains of pain and exhibits behavior of fear and fatigue. 21 Pharmacological analgesia with opioids is necessary to provide pain relief and to alleviate the suffering of the child and family.…”
Section: Discussionmentioning
confidence: 99%